Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/jhg.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-A*02:06 and HLA-DRB1*04:05 with clinical subtypes of juvenile idiopathic arthritis

Abstract: Juvenile idiopathic arthritis (JIA) is one of the most common forms of pediatric chronic arthritis. JIA is a clinically heterogeneous disease. Therefore, the genetic background of JIA may also be heterogeneous. The aim of this study was to investigate associations between human leukocyte antigen (HLA) and susceptibility to JIA and/or uveitis, which is one of the most devastating complications of JIA. A total of 106 Japanese articular JIA patients (67 with polyarthritis and 39 with oligoarthritis) and 678 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…Similarly, an association between HLA-SE and susceptibility to JIA has been reported in Caucasians [ 8 ]. We have previously reported that HLA-DRB1*04:05, a major SE-containing allele, is associated with polyarticular JIA also in the Japanese population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an association between HLA-SE and susceptibility to JIA has been reported in Caucasians [ 8 ]. We have previously reported that HLA-DRB1*04:05, a major SE-containing allele, is associated with polyarticular JIA also in the Japanese population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in frequency of the DRB1*04:05 allele showed a positive correlation (increased susceptibility) in our study; however, previous studies in Asian populations revealed a negative correlation (decreased susceptibility) in NMO patients (Figure 3) 9,15,18,20 . This same allele was associated with other autoimmune diseases in Asian populations 30,31 . In addition, a positive relationship of the allele *16:02 was found in our study, which was similar to others studies in Asian populations ( Figure 3) 9,15,18 .…”
Section: Discussionmentioning
confidence: 73%
“…It was proven that the presence of this allele is combined with multibacillary leprosy patients in Indian population [46]. The connection between A * 02:06 and juvenile idiopathic arthritis was also stated [47]. The presented analysis did not allow the complete validation of the proposed models.…”
mentioning
confidence: 89%